A Multiple-Arm, Cluster-Randomized Impact Evaluation of the Clean India (Swachh Bharat) Mission Program in Rural Punjab, India - Andres, Luis (World Bank, Washington, DC, 2020)
This study reports the findings of a large-scale, multiple-arm, cluster-randomized control study carried out in rural Punjab, India, to assess the impact of a flagship sanitation program of the Government of India. The program, the Clean India Mission for Villages, was implemented between October 2014 and October 2019 and aimed to encourage the construction of toilets, eliminate the practice of open defecation, and improve the awareness and practice of good hygiene across rural India. It utilized a combination of behavioral change campaigns, centered on the community-led total sanitation approach, and financial incentives for eligible households. The study also evaluates the incremental effects of intensive hygiene awareness campaigns in selected schools and follow-up initiatives in selected communities. The study finds that the coverage of “safely managed” toilets among households without toilets increased by 6.8–10.4 percentage points across various intervention arms, compared with a control group. Open defecation was reduced by 7.3–7.8 percentage points. The program also had significant positive impacts on hygiene awareness among adults and children, although the interventions of school campaigns and intensive follow-up were of limited additional impact.